Effect of in situ poly(ethylene terephthalate) (PET) microfibrils on the morphological structure and crystallization behavior of isotactic polypropylene (iPP) under an intensive shear rate. (18th June 2015) - Zhao, Zhongguo; Yang, Qi; Xiang, Zhang; Kong, Miqiu; Tang, Dahang; Huang, Yajiang; Liao, Xia; Niu, Yanhua
<x xml:space="preserve">Abstract</x> The morphological structure and crystallization behavior of in situ poly(ethylene terephthalate) (PET)/isotactic polypropylene (iPP) microparts prepared through micro‐injection molding are investigated using a polarized light microscope, differential scanning calorimeter, scanning electron microscope, and two‐dimensional wide‐angle X‐ray. Results indicate that both the shear effect and addition of PET fibers greatly influence the morphologies of the iPP matrix. Typical "skin‐core" and oriented crystalline structures (shish‐kebab) may simultaneously be observed in neat iPP and iPP/PET microparts. The presence of PET phases reveals significant nucleation ability for iPP crystallization. High concentrations of PET phases, especially long PET fibers, correspond to rapid crystallization of the iPP matrix. The occurrence of PET microfibrils decreases the content and size of β‐crystals; by contrast, the orientation degree of β‐crystals increases with increasing PET content in the microparts. This result suggests that the existence of the microfibrillar network can retain the ordered clusters and promote the development of oriented crystalline structures to some extent. Copyright © 2015 John Wiley & Sons, Ltd.